2022
DOI: 10.1186/s13018-022-03071-y
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors for postoperative pneumonia following surgically treated hip fracture in geriatric patients: a retrospective cohort study

Abstract: Objective Large sample investigations for risk factors for pneumonia in elderly patients after hip fracture surgeries are lacking. The purpose of this study is to determine the incidence and risk factors for postoperative pneumonia in geriatric patients following hip fracture operations. Methods A retrospective study of incidence and risk factors in a tertiary referral center between 2016 and 2020 was conducted. Geriatric patients who developed pos… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 42 publications
1
21
0
Order By: Relevance
“…2h). However, after sensitivity analysis by eliminating two studies with sample sizes <1000, 9,12 the I 2 value for the five other studies 4–8 decreased to 48%, and the significance remained unchanged ( OR = 2.19, 95% CI : 1.75–2.74, P < 0.0001), indicating the reliability of the result (Fig. S1e).…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…2h). However, after sensitivity analysis by eliminating two studies with sample sizes <1000, 9,12 the I 2 value for the five other studies 4–8 decreased to 48%, and the significance remained unchanged ( OR = 2.19, 95% CI : 1.75–2.74, P < 0.0001), indicating the reliability of the result (Fig. S1e).…”
Section: Resultsmentioning
confidence: 92%
“…Seven of the 10 included studies were conducted in China. In nine of the 10 studies, [4][5][6][8][9][10][11][12][13] the average or median age of the participants was >70 years. In the one other study, the patient distribution across different age groups were reported rather than the average age; however, age >65 years was one of the inclusion criteria.…”
Section: The General Characteristic Of the Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Several recent studies have demonstrated that low Hb level is an independent risk factor for POP in elderly patients with hip fracture [4,9], but there is also controversial report [10] and currently no cut-off value of Hb level is available. Therefore, this study retrospectively collected and analyzed the clinical data of elderly patients with hip fracture in our hospital, aiming to explore the quantitative correlation between Hb level and POP in elderly patients with hip fracture at admission, thus providing a reference level of Hb to guide preoperative blood transfusion in elderly patients with anemia.…”
Section: Introductionmentioning
confidence: 99%